Effect of silica surface on luminescence properties of tb3+-glutamic acid. - Jorge, Juliana; Verelst, M.; Castro, Gustavo Rocha de [UNESP]; Martines, Marco Antonio Utrera (My University, 2013)
We studied the effect of silica surface on luminescence properties of terbium complex by spectroscopy characterization, where microparticles of mesoporous silica type MSU-X was prepared. We used silica with different surface: calcined, washed, functionalized with 3- aminopropyl-triethoxysilane (APTES), and 3-glycidoxypropyl-trimethoxysilane (GPTMS); impregnated with Tb3+-glutamic acid complex. The obtained materials were characterized by scanning electron microscopy, porosity measurements, small-angle X-ray scattering, as structural characterization; Fourier transform infrared and luminescence spectroscopy, as spectroscopy characterization. Finally, we observed that functional groups at the silica surface lead to changes on luminescent properties of the final materials. The observed shift of the absorption and emission bands can be assigned to the effect of the functional groups of mesoporous silica.
Keywords: Lanthanide ions; 3-amino-propyl-triethoxysilane; 3-glycidoxy-propyl-trimethoxysilane